Rapid Explainability for Skill Description Learning - Demir, Caglar; Himmelhuber, Anna; Liu, Yushan; Bigerl, Alexander; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2022 Posters, Demos and Industry Tracks: From Novel Ideas to Industrial Practice co-located with 21st International Semantic Web Conference {(ISWC} 2022), Virtual Conference, Hangzhou, China, October 23-27, 2022)

LSQ Framework: The LSQ Framework for SPARQL Query Log Processing - Stadler, Claus; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (Proceedings of the QuWeDa 2022: 6th Workshop on Storing, Querying and Benchmarking Knowledge Graphs co-located with 21st International Semantic Web Conference {(ISWC} 2022), Hangzhou, China, 23-27 October 2022)

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (HT ’22: 33rd ACM Conference on Hypertext and Social Media, Barcelona, Spain, 28 June 2022- 1 July 2022)

Enhancing the Accessibility of Knowledge Graph Question Answering Systems through Multilingualization - Perevalov, Aleksandr; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (16th IEEE International Conference on Semantic Computing, ICSC 2022, Laguna Hills, CA, USA, January 26-28, 2022)

Tab2Onto: Unsupervised Semantification with Knowledge Graph Embeddings - Zahera, Hamada M.; Heindorf, Stefan; Balke, Stefan; Haupt, Jonas; Voigt, Martin; Walter, Carolin; Witter, Fabian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2022 Satellite Events - Hersonissos, Crete, Greece, May 29 - June 2, 2022, Proceedings)

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics, COLING 2022, Gyeongju, Republic of Korea, October 12-17, 2022)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d’Amato, Claudia; de Melo, Gerard; Gutierrez, Claudio; Kirrane, Sabrina; Gayo, José Emilio Labra; Navigli, Roberto; Neumaier, Sebastian; Ngonga Ngomo, Axel-Cyrille; Polleres, Axel; et al. (ACM Comput. Surv.)

A survey of RDF stores & SPARQL engines for querying knowledge graphs - Ali, Waqas; Saleem, Muhammad; Yao, Bin; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille (VLDB J.)

Hardware-agnostic computation for large-scale knowledge graph embeddings - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Softw. Impacts)

Secure learning-based MPC via garbled circuit - Tjell, Katrine; Schluter, Nils; Binfet, Philipp; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Encrypted dynamic control with unlimited operating time via FIR filters - Schluter, Nils; Neuhaus, Matthias; Schulze Darup, Moritz (2021 European Control Conference (ECC))

Tailored neural networks for learning optimal value functions in MPC - Teichrib, Dieter; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Behavioral Economics for Human-in-the-Loop Control Systems Design: Overconfidence and the Hot Hand Fallacy - Protte, Marius; Fahr, Rene; Quevedo, Daniel E. (IEEE Control Systems)
Keywords: Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering; Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering

„LauRa - In der Lehramtsausbildung Reflexionskompetenz analysieren“. Untersuchungen zum Verhältnis von Theorie, Praxis und Reflexion im Rahmen der Professionalisierung angehender Lehrpersonen. - Meier, Jana
Der Förderung von Reflexionskompetenz wird für die Professionalisierung angehender Lehrkräfte eine hohe Bedeutung für die Relationierung zwischen Theorie und Praxis zugeschrieben. In dieser Arbeit wird den übergeordneten Fragestellungen nachgegangen, inwiefern es Lehramtsstudierenden durch Reflexionsgelegenheiten im Studium gelingt, ihr theoretisches Wissen mit praktischen Erfahrungen in Beziehung zu setzen und in welchem Zusammenhang die Reflexionskompetenz zu bestimmten Fördermaßnahmen (Portfolioarbeit) und Settings (Microteaching) sowie zu anderen Facetten professioneller Handlungskompetenz (Professionswissen, Einstellungen, Motivation) steht. Auf Basis einer kompetenztheoretischen Modellierung von Reflexion wurde hierzu die Reflexionsperformanz von Lehramtsstudierenden erfasst, um Rückschlüsse auf reflexionsbezogene Denkprozesse ziehen zu können. Die Auswertungen erfolgten qualitativ inhaltsanalytisch und wurden an teilweise quantifiziert, um statistische Analysen durchführen zu können. Insgesamt zeigen die Befunde der drei Teilstudien, dass die Reflexionsperformanz insbesondere dann von höherer Qualität ist, wenn theoretische Inhalte explizit mit praktischen Erfahrungen relationiert werden. Positive Einstellungen gegenüber Reflexion unterstützen die Reflexionsperformanz. Das bildungswissenschaftliche Professionswissen der Studierenden kann darüber hinaus Unterschiede in der Reflexionsperformanz erklären.

„Reflexion ist erzwungenes Nachdenken“ – Zusammenhänge zwischen dem Reflexionsverständnis Lehramtsstudierender & Facetten ihrer Reflexionskompetenz. - Meier, Jana; Vogelsang, Christoph; Watson, Christina; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Der Zyklus von Planung und Reflexion – Zusammenhänge zwischen der generischen Unterrichtsplanungsfähigkeit und der Reflexionskompetenz angehender Lehrkräfte. - Meier, Jana; Küth, Simon; Scholl, Daniel; Vogelsang, Christoph; Watson, Christina

Erfassung der Reflexionskompetenz angehender Lehrpersonen mittels (offener) Situationsvignetten. - Meier, Jana; Vogelsang, Christoph

Rollenspiele als Übungs- & Prüfungsformate in der universitären Lehramtsausbildung. - Meier, Jana; Vogelsang, Christoph; Wotschel, Philipp; Janzen, Thomas

Einschätzungen Studierender zu Prüfungsformaten im Lehramtsstudium. - Vogelsang, Christoph; Meier, Jana; Wotschel, Philipp; Janzen, Thomas

Validierung von Testinstrumenten durch Testmotivationsindikatoren. - Watson, Christina; Meier, Jana; Küth, Simon; Scholl, Daniel; Seifert, Andreas; Vogelsang, Christoph

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Regularity of Lie groups - Hanusch, Maximilian (Communications in Analysis and Geometry)
Keywords: regularity of Lie groups

Analysis 1 und 2 Skript/Buch - Hanusch, Maximilian

Tackling the Accuracy–Interpretability Trade-off: Interpretable Deep Learning Models for Satellite Image-based Real Estate Appraisal - Kucklick, Jan-Peter; Müller, Oliver (ACM Transactions on Management Information Systems)
Deep learning models fuel many modern decision support systems, because they typically provide high predictive performance. Among other domains, deep learning is used in real-estate appraisal, where it allows to extend the analysis from hard facts only (e.g., size, age) to also consider more implicit information about the location or appearance of houses in the form of image data. However, one downside of deep learning models is their intransparent mechanic of decision making, which leads to a trade-off between accuracy and interpretability. This limits their applicability for tasks where a justification of the decision is necessary. Therefore, in this paper, we first combine different perspectives on interpretability into a multi-dimensional framework for a socio-technical perspective on explainable artificial intelligence. Second, we measure the performance gains of using multi-view deep learning which leverages additional image data (satellite images) for real estate appraisal. Third, we propose and test a novel post-hoc explainability method called Grad-Ram. This modified version of Grad-Cam mitigates the intransparency of convolutional neural networks (CNNs) for predicting continuous outcome variables. With this, we try to reduce the accuracy-interpretability trade-off of multi-view deep learning models. Our proposed network architecture outperforms traditional hedonic regression models by 34% in terms of MAE. Furthermore, we find that the used satellite images are the second most important predictor after square feet in our model and that the network learns interpretable patterns about the neighborhood structure and density.
Keywords: Interpretability; Convolutional Neural Network; Accuracy-Interpretability Trade-Of; Real Estate Appraisal; Hedonic Pricing; Grad-Ram

Correction: Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehmann, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Keywords: Orthopedics and Sports Medicine

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Hyphenation of ultra-high-performance liquid chromatography and ion mobility mass spectrometry for the analysis of sequence-defined oligomers with different functionalities and tacticity - Berg, Marie-Theres; Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
In recent years, sequence-defined oligomers (SDOs) gained increasing interest due to their perfectly controlled molecular structure, thus providing defined properties. In order to tune the properties, different functionalities need to be incorporated into the oligomers and the chain tacticity needs to be controlled. Beside the synthesis of SDOs, suitable methods need to be found to analyze the molecular structure. In this work, oligomers exhibiting an alternating or block-wise sequence of side chain functionalities were analyzed using a hyphenation of ultra-high-performance liquid chromatography and electrospray ionization mass spectrometry enhanced by ion mobility separation (IMS). Moieties in the side chains were varied according to polarity and bulkiness. Moreover, chain tacticity was varied. Drift times in the IMS cell and the corresponding collision cross section (CCS) values were shown to be individual parameters allowing the identification of SDOs, even in the case that SDO structures only differ in sequence or tacticity of side chain functionalities. Thus, a library of CCS values was obtained as reference used for the analysis of complex mixtures of SDOs.
Keywords: Ultra-high-performance liquid chromatography; ion mobility separation; mass spectrometry; LC-MS hyphenation; sequence-defined oligomers

Quinuclidine-Immobilized Porous Polymeric Microparticles as a Compelling Catalyst for the Baylis–Hillman Reaction - Kumar, Amit; Kuckling, Dirk; Nebhani, Leena (ACS Applied Polymer Materials)
Poly(quinuclidin-3-yl methacrylate-co-divinylbenzene) microparticles having porous as well as nonporous morphology and varying contents of quinuclidine functionality were synthesized by distillation–precipitation polymerization. Further, the synthesized microparticles were explored to catalyze the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Porous and nonporous microparticles functionalized with a catalytic moiety with a loading of 70% (labeled as P70 and NP70) were employed to optimize reaction parameters such as water content, solvent, and temperature for the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Using optimal conditions, the catalytic efficiency of porous and nonporous microparticles at different feed compositions was determined. Porous microparticles containing 70% of quinuclidine (P70) displayed 100% conversion within 16 h at 50 °C, while nonporous microparticles containing 70% of quinuclidine (NP70) displayed a relatively less catalytic conversion, which is attributed to their lower surface area. Furthermore, the catalytic activity of porous microparticles containing 70% of quinuclidine (P70) for the Baylis–Hillman reaction involving a variety of aryl aldehyde derivatives was determined, where the microparticles displayed impressive catalytic efficiency. In addition, the reusability of the microparticles functionalized with a catalytic moiety was evaluated for five cycles of catalytic reaction.
Keywords: distillation−precipitation polymerization; porous microparticles; heterogeneous catalysis Baylis−Hillman reaction; reusable catalyst

Branching analysis of β-cyclodextrin-based poly(N-isopropylacrylamide) star polymers using triple detection SEC - Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
For the first time, poly(N-isopropylacrylamide) (PNIPAAm) star polymers with a β-cyclodextrin core are characterized in detail by size-exclusion chromatography (SEC) with triple detection to experimentally verify the number of arms. A combination of a refractive index detector, multi-angle laser light scattering detector, and an online-viscosimeter was used for branching analysis. At first, the SEC system was calibrated and the detector setup was validated using linear polystyrene reference polymers. The applicability of the established triple detection SEC for branching analysis was shown by the analysis of two commercially available polystyrene star polymers. Due to the high molar masses of the star polymers, both the contraction ratio g and g′ could be determined independently, thus allowing the calculation of the viscosity shielding ratio ε. Finally, the branching analysis of the PNIPAAm star polymers could experimentally confirm the assumed arm number of up to 21 arms. Moreover, an increasingly compact molecular structure and the influence of the arm number on the viscosity shielding ratio could be shown.
Keywords: Size-exclusion chromatography; triple detection; branching analysis; star polymers; poly(N-isopropylacrylamide); β-cyclodextrin

Uniqueness of the Inverse First Passage Time Problem and the Shape of the Shiryaev boundary - Kolb, Martin; Klump, Alexander (Theory of Probability and its Applications)

Does education have an impact on patience and risk willingness? - Tawiah, Beatrice Baaba (Applied Economics)

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Persistence of autoregressive sequences with logarithmic tails - Denisov, Denis; Hinrichs, Günter; Kolb, Martin; Wachtel, Vitali (Electronic Journal of Probability)
We consider autoregressive sequences Xn = aXn−1 + ξn and Mn = max{aMn−1 , ξn} with a constant a ∈ (0, 1) and with positive, in- dependent and identically distributed innovations {ξk }. It is known that if P(ξ1 > x) ∼ d log x with some d ∈ (0, − log a) then the chains Xn and Mn are null recurrent. We investigate the tail behaviour of recurrence times in this case of logarithmically decaying tails. More precisely, we show that the tails of recurrence times are regularly varying of index −1 − d/ log a. We also prove limit theorems for Xn and Mn conditioned to stay over a fixed level x0. Furthermore, we study tail asymptotics for recurrence times of Xn and Mn in the case when these chains are positive recurrent and the tail of log ξ1 is subexponential.

Green Deals Gain Steam - Kengelbach, Jens; Keienburg, Georg; Söllner, Tobias; Wang, Yiran; Sievers, Sönke; Friedmann, Daniel; Nielsen, Jesper (BCG M&A Report 2022)

Do Green Deals Create Value? - Kengelbach, Jens; Friedman, Daniel; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Wang, Yiran; Sievers, Sönke (BCG M&A Report 2022)

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Schärfung der Sinne. Josef Winklers Mikroästhetik im Kontext kleiner Prosaformen der Moderne - Öhlschläger, Claudia (Inter- und transmediale Ästhetik bei Josef Winkler)

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Alfred Anderschs "Die Rote" mit Antonioni gelesen - Öhlschläger, Claudia (Das Italien des Alfred Andersch. Interkulturelle und intermediale Konstellationen)

Lattice Revocation Mechanisms - Lohse, Jan

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Exploring the effects of physics explainer videos and written explanations on declarative knowledge and the illusion of understanding - Kulgemeyer, Christoph; Hörnlein, Madeleine; Sterzing, Fabian (International Journal of Science Education)
Keywords: Education

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Democracy ≠ Democracy. Creating digital infographics to compare different democratic systems. - Janzen, Thomas (Englisch betrifft uns)

Geschlechtsidentität - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Sexuelle Orientierung - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Schlussbericht: Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) Entwicklung und Evaluation eines interdisziplinären Fortbildungsangebots - Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia; Neumann, Phillip; Grüter, Sandra; Weber, Antonia

Der Rollenhut als Vermittlungsmedium - Rollenklärungsprozesse im Kontext multiprofessioneller Kooperationen als Thema universitärer Aus- und Fortbildungen von Lehrkräften und Sozialpädagog*innen - Neumann, Phillip; Hopmann, Benedikt; Lütje-Klose, Birgit (Herausforderung Lehrer*innenbildung - Zeitschrift zur Konzeption, Gestaltung und Diskussion)
Multiprofessionelle Kooperation zwischen allgemeinen und sonderpädagogischen Lehrkräften und mit weiteren Fachkräften, u.a. der Schulsozialarbeit, der Schulpsychologie und mit Schulbegleitungen, gilt bei der Entwicklung inklusiver Schulen als zentrale Stellschraube. Dementsprechend wird Kooperation im Kontext Schule auch in der universitären Ausbildung von zukünftig miteinander kooperierenden Professionen sowie in Fortbildungen für Lehrkräfte und multiprofessionelle Teams verstärkt ins Blickfeld gerückt. Zugleich lässt sich beobachten, dass in inklusiven Schulen bislang vermeintlich klare Zuständigkeiten, insbesondere zwischen Sonder- und Sozialpädagog*innen, aufweichen und neu austariert werden müssen. Bei der Entwicklung multiprofessioneller Teams gilt die Klärung von Rollen und Aufgaben als eine besondere Herausforderung, wenn unterschiedliche Professionen mit unterschiedlichen institutionellen Anbindungen und pädagogischen Zielperspektiven oder Grundhaltungen mitei-nander kooperieren. Das vorgestellte Instrument – der Rollenhut – dient dazu, in multiprofessionellen Gruppen eine individuelle Reflexion über die eigenen Aufgaben anzustoßen und auf dieser Grundlage gemeinsam über die gegenseitigen Erwartungen und Rollen zu diskutieren. Das Instrument wurde im Kontext von Fortbildungen multiprofessioneller Teams an Schulen konzipiert und auch im Rahmen der universitären Lehrer*innenbildung erprobt.

Teachers Between a Rock and a Hard Place: Goal Conflicts Affect Teaching Motivation Mediated by Basic Need Satisfaction - Gorges, Julia; Neumann, Phillip; Störtländer, Jan Christoph (Frontiers in Psychology)
Teaching is a highly demanding profession that requires handling multiple and potentially contradictory goals. Therefore, it is likely that teachers experience conflict between work-related goals on a daily basis. Intraindividual goal conflict may occur when individuals pursue multiple goals drawing on the same limited resources (resource-based goal conflict), or when two or more goals are incompatible in terms of goal attainment strategy or desired end states (inherent goal conflict). Because goal conflict is typically associated with negative effects such as attenuated motivation and wellbeing, teacher goal conflict may jeopardize teaching motivation. This cross-sectional study investigated the effects of in-service teachers’ ( N = 302) goal conflicts on their autonomous (intrinsic and identified regulation) and controlled (introjected and extrinsic regulation) teaching motivation and tested the satisfaction of teachers’ basic need for autonomy, competence, and relatedness as mediators. In line with our hypotheses, results from structural equation modeling showed that frequently experiencing resource-based goal conflict leads to a lower satisfaction of the basic need for autonomy, which, however, was unrelated to teaching motivation. In contrast, frequently experiencing inherent goal conflict attenuates the satisfaction of the basic need for competence, which, in turn, positively predicted autonomous teaching motivation and negatively predicted extrinsic regulation. As expected, relatedness was not associated with the experience of goal conflict. The discussion focuses on differential effects of the two types of goal conflict on teaching motivation and on the relevance to expand research on teachers’ intraindividual goal conflicts.
Keywords: General Psychology

Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) : Technical Report V. 1.0 - Gorges, Julia; Neumann, Phillip; Wild, Elke; Lütje-Klose, Birgit; Grüter, Sandra; Weber, Antonia; Senior, Jonathan

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Development of a crash behaviour prediction method for resistance spot welded 3-steel sheet joints - Olfert, Viktoria; Meschut, Gerson; Hein, David; Schuster, Lilia; Sommer, Silke
The recent trend towards extensive electric mobility leads to a variety of new challenges for the engineering of future vehicle concepts. One particular challenge is the additional weight added to the vehicle by the battery, which stands in direct contrast to the existing customer expectation of a high driving range. The reduction of the total vehicle weight is driven by the extensive use of ultra-high-strength steels in thin sheet thicknesses in car body construction. Resistance spot welding is the dominant joining process in steel-intensive lightweight construction due to its high degree of automation, process reliability and the associated economic efficiency. In order to comply limitations of the space in the vehicle body and to ensure the most efficient use of materials in lightweight construction, joints are used that connect several sheets with a single spot weld. This leads to new challenges for the prediction of the load-bearing capacity and failure behaviour under crash loading. This paper presents a systematic characterisation of 3 sheet steel joints in order to find formulary, empirical relationships between the load-bearing capacity of the joint and the affecting parameters. Numerical simulations are carried out in order to clarify the causes of occurring phenomena in experiments. For this purpose, influencing variables such as joint strength, joint arrangement, sheet thickness, sheet strength, load type and load case on the load bearing capacity and failure behaviour are identified. Furthermore, the extent to which the behaviour of 2-sheet joints can be transferred to 3-sheet joints is investigated. A formulary correlation enables a quick and inexpensive estimates of the load-bearing capacity of 3-sheet metal connections. These models can be used for a computer-efficient simulation of components with three layered spot welded joints.

Wideband SiN pulse interleaver for optically-enabled analog-to-digital conversion: a device-to-system analysis with cyclic equalization - Zazzi, Andrea; Müller, Juliana; Ghannam, Ibrahim; Battermann, Moritz; Rajeswari, Gayatri Vasudevan; Weizel, Maxim; Scheytt, J. Christoph; Witzens, Jeremy (Optics Express)
We present the design and experimental characterization of a silicon nitride pulse interleaver based on coupled resonator optical waveguide filters. In order to achieve a targeted free spectral range of 1.44 THz, which is large given the reduced optical confinement of the silicon nitride platform, individual ring resonators are designed with tapered waveguides. Its application to time-interleaved photonically-assisted ADCs is analyzed by combining experimental characterization of the photonic integrated circuit with a comprehensive model of the entire ADC. The impact of fundamental signal distortion and noise sources affecting the converter is investigated and suitable equalization techniques at the digital signal processing level are evaluated. The novel application of a simple but powerful equalization filter in the DSP domain allows for a significant improvement of the digitized signal SNR. An ENOB of 5 over a 75 GHz bandwidth (150 GS/s) and an ENOB of 4.3 over a 100 GHz bandwidth (200 GS/s) are expected to be achievable with compact and off-the-shelf single-section semiconductor mode locked lasers, that can be further improved with lower noise light sources.

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

'Women’s work is never easy, never clean': (Strong) Black Womanhood and the Carceral State in Tayari Jones’s An American Marriage - Hartmann, Alexandra (U.S. American Culture as Popular Culture)

Nothing Ever Ends: Critical Race Theory, Schwarzer Humanismus und Watchmen - Hartmann, Alexandra (Alle Uns: Differenz, Identität, Repräsentation)

Validation of the student version of the Perceptions of Inclusion Questionnaire in primary and secondary education settings - Knickenberg, Margarita; Zurbriggen, Carmen L. A.; Schwab, Susanne (SAGE Open)
Considering students’ voices and perspectives is indispensable in educational contexts. Therefore, instruments of measurement that are reliable and valid and can be used easily without complications are needed in schools. The Perceptions of Inclusion Questionnaire (PIQ) is a short instrument used to assess three central dimensions of inclusion, namely emotional and social inclusion and academic self-concept. Previous evaluations indicate in general high psychometric properties. This study aimed to evaluate the construct validity of the three scales of the PIQ’s student version using different approaches in two samples from primary (grade 4, N = 721) and secondary (grade 7, N = 393) schools. The results of confirmatory factorial analyses confirmed the PIQ’s three factors in both samples which are also measurement equivalent across grades. Plausible correlations with additional divergent and convergent scales reveal that the PIQ measures the theoretically assumed constructs—emotional and social inclusion as well as academic self-concept—validly.
Keywords: General Social Sciences; General Arts and Humanities

Recht und Wirtschaft in Europa, Bd. 1: Lüke: Reverse Factoring - Eine rechtliche und ökonomische Analyse - Krimphove, Dieter

Internationale Schiedgerichtsbarkeit: Perspektiven für die Wirtschaft - Krimphove, Dieter

MaRisk: Kommentar: Rundschreiben 10/2021 (BA) - Mindestanforderung an das Risikomanagement - Krimphove, Dieter; Lüke, Christoph

Völkerrecht und IPR - Krimphove, Dieter; Lentner, Gabriel

Kapitalmarktrecht - Krimphove, Dieter; Lüke, Christoph

Brave New Kachel-World? Über Zoom-Booming, Datenkontrolle und öffentliche Infrastrukturen - Weber, Jutta (Von Menschen und Maschinen – Mensch-Maschine-Interaktionen in digitalen Kulturen)

Ende des werberechtlichen Schattendaseins der "Hörmarke" - Zugleich eine Analyse von EuG "Ardagh Metal Beverage/EUIPO" - Krimphove, Dieter (Zeitschrift für Gewerblichen Rechtsschutz und Urheberrecht)

Die Körordnung im deutschen und Europäischen Recht - Krimphove, Dieter; Schlief, Till (Natur und Recht NuR)

Mehr Geld ohne Mehrarbeit? - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Geldwäsche: Tatbestände, Aufgriffsmöglichkeiten, Indizien im Zahlungs- und Kapitalmarkt - Krimphove, Dieter; Ikemeyer, Raphael (Compliance Berater)

Der EuGH und die Rechtsstaatlichkeit Polens - Anmerkung zum Urteil des EuG v. 9.2.2922, Rs. T-791/19 (Sped-Pro) - Krimphove, Dieter (Europarecht)

Neobanken - Regelungslücke im Aufsichtsrecht? - Krimphove, Dieter; Knoblich, René (Compliance Berater)

Der EuGH und der ersatzlose Verfall des Jahresurlaubes - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Cross-Compliance im Umweltschutz und Landwirtschaft - Krimphove, Dieter (Natur und Recht)

Schlussbericht ITS.ML: Intelligente Technische Systeme der nächsten Generation durch Maschinelles Lernen. Forschungsvorhaben zur automatisierten Analyse von Daten mittels Maschinellen Lernens - Hammer, Barbara; Hüllermeier, Eyke; Lohweg, Volker; Schneider, Alexander; Schenck, Wolfram; Kuhl, Ulrike; Braun, Marco; Pfeifer, Anton; Holst, Christoph-Alexander; Schmidt, Malte; Schomaker, Gunnar; Tornede, Tanja

Light Scattering by Large Densely Packed Clusters of Particles - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Springer Series in Light Scattering - Volume 8: Light Polarization and Multiple Scattering in Turbid Media)
We review our results of numerical simulations of light scattering from different systems of densely packed irregular particles. We consider spherical clusters, thick layers and monolayers with realistic topologies and dimensions much larger than the wavelength of light. The maximum bulk packing density of clusters is 0.5. A numerically exact solution of the electromagnetic problem is obtained using the Discontinuous Galerkin Time Domain method and with application of high- performance computing. We show that high packing density causes light localization in such structures which makes an impact on the opposition phenomena: backscattering intensity surge and negative linear polarization feature. Diffuse multiple scattering is significantly reduced in the case of non-absorbing particles and near-field interaction results in a percolation-like light transport determined by the topology of the medium. With this the negative polarization feature caused by single scattering gets enhanced if compared to lower density samples. We also confirm coherent double scattering mechanism of negative polarization for light scattered from dense absorbing slabs. In this case convergent result for the scattering angle polarization dependency at backscattering can be obtained for a layer of just a few tens of particles if they are larger than the wavelength.
Keywords: tet_topic_scattering

Schnittstellenaufgaben in der Analysis I zur Verknüpfung von Schul- und Hochschulmathematik - Aufgabenbeispiele und Ergebnisse einer Evaluationsstudie. - Hoffmann, Max; Biehler, Rolf (Bedarfsgerechte fachmathematische Lehramtsausbildung. Analyse, Zielsetzungen und Konzepte unter heterogenen Voraussetzungen)

Fachwissen als Grundlage fachdidaktischer Urteilskompetenz – Beispiele für die Herstellung konzeptueller Bezüge zwischen fachwissenschaftlicher und fachdidaktischer Lehre im gymnasialen Lehramtsstudium - Biehler, Rolf; Hoffmann, Max (Professionsorientierte Fachwissenschaft. Kohärenzstiftende Lerngelegenheiten für das Lehramtsstudium Mathematik)